(untitled) (El-Wahat Journal for Research and Studies, 2025)
In this research I deal with the subject of the Arabic language, the language of science and literature for many centuries in all countries ruled by Muslims, which were among the most important manifestations of civilization, but they were considered one of the issues that have nothing to do with history despite their organic link to it as a product, but the search for the extent of its spread between the East (Persia) And the West (the Islamic Maghreb) showed a lot about it and proved that it is one of the historical problems that must be studied and researched because it reflects the cultural stock of the nation, and from here it is possible to address the problem of the spread of the Arabic language and how it was able to spread in Morocco in a remarkable way that it is totally linked to religion and what the law dictates. Unlike Persia, in which the Islamic religion prevailed and the Arabic language was restricted, and I will study the reasons and factors that contributed to its spread and the obstacles that led to its isolation. Key words: Arabic language, Islam, Islamic Maghreb, Persia , Arab Tribes